Cardiovascular magnetic resonance in emergency patients with multivessel disease or unobstructed coronary arteries: a cost-effectiveness analysis in the UK. Issue 7 (11th July 2019) - Stokes, Elizabeth A; Doble, Brett; Pufulete, Maria; Reeves, Barnaby C; Bucciarelli-Ducci, Chiara; Dorman, Stephen; Greenwood, John P; Anderson, Richard A; Wordsworth, Sarah
Abstract : Objective: To identify the key drivers of cost-effectiveness for cardiovascular magnetic resonance (CMR) when patients activate the primary percutaneous coronary intervention (PPCI) pathway. Design: Economic decision models for two patient subgroups populated from secondary sources, each with a 1 year time horizon from the perspective of the National Health Service (NHS) and personal social services in the UK. Setting: Usual care (with or without CMR) in the NHS. Participants: Patients who activated the PPCI pathway, and for Model 1: underwent an emergency coronary angiogram and PPCI, and were found to have multivessel coronary artery disease. For Model 2: underwent an emergency coronary angiogram and were found to have unobstructed coronary arteries. Interventions: Model 1 (multivessel disease) compared two different ischaemia testing methods, CMR or fractional flow reserve (FFR), versus stress echocardiography. Model 2 (unobstructed arteries) compared CMR with standard echocardiography versus standard echocardiography alone. Main outcome measures: Key drivers of cost-effectiveness for CMR, incremental costs and quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios. Results: In both models, the incremental costs and QALYs between CMR (or FFR, Model 1) versus no CMR (stress echocardiography, Model 1 and standard echocardiography, Model 2) were small (CMR: −£64 (95% CI −£232 to £187)/FFR: £360 (95% CI −£116 to £844) and CMR/FFR: 0.0012 QALYs (95% CI −0.0076 to 0.0093)) and (£98 (95% CI −£199 to £488) and 0.0005 QALYs (95% CI −0.0050 to 0.0077)), respectively. The diagnostic accuracy of the tests was the key driver of cost-effectiveness for both patient groups. Conclusions: If CMR were introduced for all subgroups of patients who activate the PPCI pathway, it is likely that diagnostic accuracy would be a key determinant of its cost-effectiveness. Further research is needed to definitively answer whether revascularisation guided by CMR or FFR leads to different clinical outcomes in acute coronary syndrome patients with multivessel disease.